2004
DOI: 10.1007/s11255-004-0922-1
|View full text |Cite
|
Sign up to set email alerts
|

Prostate cancer with bladder neck involvement: Pathologic findings with application of a new practical method for tumor extent evaluation and recurrence-free survival after radical prostatectomy

Abstract: Bladder neck involvement correlates with pathologic unfavorable findings on radical prostatectomy specimens as well as to preoperative PSA levels. However, the PSA-recurrence risk associated with bladder neck involvement (pT4) was similar to extraprostatic extension (pT3a) and substantially lower than seminal vesicle invasion (pT3b). The findings favor a need for downstaging of bladder neck involvement in the next version of the TNM system. The method proposed for tumor extent evaluation is simple and accessib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 20 publications
0
27
0
Order By: Relevance
“…Most of the previous studies [4][5][6][7]20 have found that bladder neck involvement carries a risk of progression similar to extraprostatic extension and lower than seminal vesicle invasion and suggested to consider downstaging bladder neck involvement in the TNM staging system. However, the lack of a consistent pathological definition of bladder neck involvement in different studies complicates the accurate determination of prognostic significance of microscopic bladder neck involvement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the previous studies [4][5][6][7]20 have found that bladder neck involvement carries a risk of progression similar to extraprostatic extension and lower than seminal vesicle invasion and suggested to consider downstaging bladder neck involvement in the TNM staging system. However, the lack of a consistent pathological definition of bladder neck involvement in different studies complicates the accurate determination of prognostic significance of microscopic bladder neck involvement.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7][8] The College of American Pathologists practice protocol on prostate specifically states that 'microscopic involvement of bladder neck muscle fibers in radical prostatectomy specimens should not be equated with a pT4 designation.' pT4 generally requires 'gross involvement of the bladder neck.'…”
mentioning
confidence: 99%
“…[53][54][55][56][57][58][59][60] Most studies 53,54,[58][59][60][61] have shown that bladder neck invasion carries a risk of progression similar to extraprostatic extension and lower than that of seminal vesicle invasion. This supports the concept that bladder neck invasion should be considered as pT3a disease, as these studies have shown that the prognosis of patients with bladder neck invasion is no worse than that for those with pT3 disease.…”
Section: Microscopic Bladder Neck Invasionmentioning
confidence: 99%
“…This supports the concept that bladder neck invasion should be considered as pT3a disease, as these studies have shown that the prognosis of patients with bladder neck invasion is no worse than that for those with pT3 disease. [53][54][55]57,[61][62][63] There is controversy as to whether microscopic bladder neck invasion remains an independent histological prognostic factor and predicts disease progression after radical prostatectomy. Some investigators have found that bladder neck invasion is associated with other well-established poor prognostic features such as higher Gleason score and serum PSA, extraprostatic extension, seminal vesicle invasion, positive surgical margins, positive lymph nodes and extensive tumor volume.…”
Section: Microscopic Bladder Neck Invasionmentioning
confidence: 99%
“…of maximum tumor area using a single or multiple slide approach, 50 counting of the number of involved blocks, 51 assessment of the positive to negative block ratio, 52 use of an integration measuring grid, 27 point counting, 53,54 naked eye examination of the glass slides after all microscopically identifiable foci of carcinoma have been circled with a marking pen, 55 or, most simply, naked eye examination of sections without marking of tumor foci. 36 Authors of several landmark studies 34,35,37,50 have put forward that measurement of size or volume may be limited to assessment of the largest tumor nodule in a prostatectomy specimen and a method that may be appropriate is measurement of the maximum diameter of the largest tumor nodule in the transverse plane, after delineating the edges of the tumor on the glass slide.…”
Section: Measurement Of Tumor Volumementioning
confidence: 99%